2022
DOI: 10.1002/sstr.202100211
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Fe‐Doped CoO Nanotubes as High‐Efficient Electrocatalysts for Oxygen Evolution Reaction

Abstract: Developing high‐performance, low‐cost, and robust electrocatalysts is of great importance to boost the efficiency of oxygen evolution reaction (OER). Herein, based on the integrated design of chemical composition and geometric structure, Fe‐doped CoO nanotubes (NTs) with high OER activity are prepared by a facile template‐free approach. The construction of this tubular structure is realized via a simple wet‐chemical reaction to prepare solid nanorods as precursor and a subsequent calcination treatment of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 41 publications
(29 reference statements)
1
24
0
Order By: Relevance
“…8,[12][13][14] This TPT feature allows the template-free facile formation of crystallographically oriented nanoporous oxides. Cobalt oxides (Co x O y ), including cobalt(II, III) oxide (Co 3 O 4 ) and cobalt(II) oxide (CoO), are among the most studied oxides prepared from LHS precursors because of their application in anode materials for lithium ion batteries, 15,16 electrochemical capacitors 17,18 and (photo)electrocatalysts for water splitting reactions (both hydrogen and oxygen evolution reactions) [19][20][21][22] and for CO 2 reduction. 23,24 Several types of cobalt-based LHSs (Co-LHSs), e.g., Co(OH) 2 , Co 2 (NO 3 )(OH) 3 and Co 7 (NO 3 ) 2 (OH) 12 , have been synthesized by means of alkaline precipitation and hydrothermal methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[12][13][14] This TPT feature allows the template-free facile formation of crystallographically oriented nanoporous oxides. Cobalt oxides (Co x O y ), including cobalt(II, III) oxide (Co 3 O 4 ) and cobalt(II) oxide (CoO), are among the most studied oxides prepared from LHS precursors because of their application in anode materials for lithium ion batteries, 15,16 electrochemical capacitors 17,18 and (photo)electrocatalysts for water splitting reactions (both hydrogen and oxygen evolution reactions) [19][20][21][22] and for CO 2 reduction. 23,24 Several types of cobalt-based LHSs (Co-LHSs), e.g., Co(OH) 2 , Co 2 (NO 3 )(OH) 3 and Co 7 (NO 3 ) 2 (OH) 12 , have been synthesized by means of alkaline precipitation and hydrothermal methods.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt oxides (Co x O y ), including cobalt( ii , iii ) oxide (Co 3 O 4 ) and cobalt( ii ) oxide (CoO), are among the most studied oxides prepared from LHS precursors because of their application in anode materials for lithium ion batteries, 15,16 electrochemical capacitors 17,18 and (photo)electrocatalysts for water splitting reactions (both hydrogen and oxygen evolution reactions) 19–22 and for CO 2 reduction. 23,24 Several types of cobalt-based LHSs (Co-LHSs), e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] Oxygen evolution reaction (OER) is a key anodic reaction of water splitting, which often constrains hydrogen production efficiency due to the sluggish kinetics of multistep electron transfer. [3][4][5][6] To lower the energy cost of electronic structure via introducing additional transition-metal species has become a more extensive modification method for LDH. [36,37] One notable example is by Sun et al, who confirmed the well-performed OER activity of W-doped FeNi-LDH, [38] and found that W doping into FeNi-LDH offered the favorable surface electronic structure and charge transfer because of the localized W 5d states, and thus optimize the intermediates adsorption energy by decreasing the G O -G HO .…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of renewable energies, such as the unpredictable availability and non-uniformity in distribution, urge the development of large-scale energy storage systems [1][2][3][4][5][6][7][8][9][10][11][12]. Among many energy storage technologies, a rechargeable battery based on the conversion between electric and chemical energy is one of the most effective methods due to its unparalleled conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%